Motor imagery as a tool to enhance the didactics in physical education and artistic gymnastic - Raiola, G.; Scassillo, I.; Parisi, F.; Di Tore, P. A. (Journal of Human Sport & Exercise, 2013)
The motor imagery is a cognitive process of mental simulation of an action in absence of physical movement. During the motor imagery the cerebral areas of the pre-motor cortex, the same which a muscular contraction would put in action, are activated. There are two methods of motor imagery: In first person - In thirdperson. The biological basis on which the motor imagery theory is founded, is formed by mirror neurons. The mirror neurons are a particular class of visual-motor neurons which permit to learn and to optimize a motor gesture without executing it. The mirror neurons are the basis for learning and understanding of motor events intentions. The artistic gymnastics is a sport of precision and the movements are complex,then it use the abilities closed skills. The artistic gymnastics uses the model of closed-loop control.According to the recruitment of energy, artistic gymnastics is a sport mainly alactacid anaerobic/lactate. Starting from these scientific assumptions the aim of this study wants to evaluate the effects and the potential benefits of motor imagery in order to contribute to the strengthening of young athletes performances in the artistic gym. Used in training in the race.